Die Diffusion der Idee der Landschaft - Hard, Gerhard (ERDKUNDE, 1996)
The most general theories of a discipline and, above all, the ultimate conceptual framework of these theories, is at least partly determined by impulses and influences whose sources lie outside science. In this sense, the following investigation starts from the assumption that the singular importance of the concept of landscape in German geography during the 20th century lies grounded in an intellectual movement which, during the time in question, extended in the German-language area well beyond geography and, indeed, well beyond science. This hypothesis is confirmed and made precise by a con tent analysis of general bibliographies. The professional interest of the geographer in the landscape is revealed as a branch of a general interest in the landscape (and, above all, the German landscape) which is characteristic of German literature since about 1900-1910 and has no parallel in other language areas. This interest found its peak at first in the literature of the aesthetic, in literary essays, in the literature of the humanities, then first in geography around 1930-1940. While the general interest, however, has been declining for about two decades, especially in literature of rank, it has lived on since 1950 in the literature of institutionalised 'landscape architecture and landscape conservation' and, in unchanged form, in academic geography. The diffusion process of the landscape concept (and the interest in the landscape) is interpreted as far as bibliographical sources allow; in addition, a framework for further study of this innovation, so important to the history of the discipline, is described.